Perkembangan Kota Tua Modern Jambi Di Bawah Keresidenan Kolonial Belanda(1906-1942) Sebagai Bahan Ajar SMA N 1 Muaro Jambi - Vivit Herawaty; Reka Seprina (SM Institute, 2023)
After the Jambi Sultanate fell in 1906, the area around the city of Muaro Tembesi was ruled by the Dutch. After this period of time, Muaro Tembesi continued to develop until today. As the former center of the Dutch government, Muaro Tembesi is now famous as the site of various Dutch-made historical buildings. The aim of this research is to find out when and why Dutch colonialism and imperialism played an important role in the growth of the contemporary metropolitan city of Muaro Tembesi. The research method uses a qualitative and descriptive approach. The research results confirm that the modern city of the Dutch era, namely Muaro Tembesi, can be used as a case study of Indonesian history and an elective subject related to history. So students can learn more about local history and contribute to its preservation by studying the Dutch heritage left behind in Muaro Tembesi today. This can also foster a greater sense of patriotism and pride that students have towards their country